A study of the relationships among environmental performance, environmental disclosure, and financial performance. Issue 1 (5th February 2018) - Lu, Lucy Wenxiang; Taylor, Martin Edward
Abstract : Purpose: The purpose of this paper is to study the relationships among environmental performance (EP), environmental disclosure (ED), and financial performance (FP) (three corporate constructs) using data from Newsweek's green rankings. Design/methodology/approach: Previous studies document mixed results about the relations among the three constructs. A firm's overall management strategy may affect the three constructs simultaneously; therefore, the interrelationships among EP, ED, and FP were jointly examined. A simultaneous equations approach was used to test the hypothesis. Findings: The three-stage least square (3SLS) estimation results show a negative relationship between EP and FP and a positive relationship between EP and ED, suggesting that financially successful firms are less likely good environmental performers but green firms are more likely to disclose their EP. Research limitations/implications: Since the sample firms examined in this study are US large-size companies, the results found in this paper may not apply to small- and/or medium-size firms or to companies in other countries. Practical implications: Three corporate constructs are jointly correlated with each one. A firm's overall strategic plan on environmental engagement is likely reflected in how it engages in each of the constructs that affect costs and benefits. Sustainable efforts, in short term, may put firms at risk. Companies may need to take a long-term perspective when cutting costs is curtailed. Originality/value: The research contributes to the ED and EP literature by using a 3SLS simultaneous equation method and analyzing a more recent and comprehensive multi-industry data. By controlling industry effect, the research investigates the interrelationships among three corporate constructs and finds interesting results. An interpretation and discussion are provided.